Permainan Tradisional Betawi untuk Meningkatkan Kemampuan Kognitif Siswa di TK Mutiara - Ahmad Syaikhu; Ahmad Durul Napis (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
This research aims to obtain data on improving cognitive abilities through Betawi’s traditional game activities through song. The study was conducted at TK Mutiara Duri Kosambi Cengkareng, West Jakarta and the subject of this research is TK Mutiara B Group children. This study used a class action research method which was carried out with two cycles. Data is obtained from observation instruments, documentary studies and field notes. Observation of pre-cycle measures obtained an average of 53.95%. In cycle 1 the average results of observations 71,042%. Then in the second cycle cognitive ability has increased 18.53%, with an average yield of 89.58%. The results of research conducted at TK Mutiara show that Betawi traditional game activities through song can improve cognitive development of young children. The implications of this study suggest that teachers should implement learning by maximizing play activities. The teacher is also encouraged to be more careful in planning and implementing learning so as to achieve the goals set.